Screening for cardiovascular risk and diabetes in the elderly at a care center for the elderly in Palmira. - Cruz-Potes, José Manuel (2022)
Objective: To determine the cardiovascular risk and diabetes in the elderly population of a center for the elderly in the municipality of Palmira. Materials and Methods: A cross-sectional descriptive study was carried out in the elderly from Palmira nursing home in the city of Palmira, who voluntarily participated in the study by signing the informed consent and who underwent a characterization and application survey of the cardiovascular risk measurement scales of the WHO and FINDRISC. Results: A total of 13 older adults from the Asilo Palmira care center for the elderly were evaluated, in which it was observed that 69% belonged to the male gender, and the mean age of the participants was 80,9 years. 46,2% present a moderate cardiovascular risk level and 30,8% a high risk level. Likewise, 38,5% of the participants had a high risk of diabetes. Conclusion: On the one hand, a greater predominance of the male gender of the participants is evident from the sociodemographic conditions. Regarding the prediction of cardiovascular risk, it is concluded that 46.2% of the population has a moderate risk of suffering a fatal cardiovascular event in a period of 10 years, with arterial hypertension being the most frequent risk factor. 69,2% of those evaluated present a low level of physical activity, which increases the risk of diabetes in this population group.